Para o que formamos? Reflexões sobre a concepção sócio alimentar do curso superior de Tecnologia em Gastronomia da UNISC - Minuzi, Gabrielle Assunção (2021)
In this research, it is proposed to present considerations on the social feeding issue, which underlies the qualification of professionals on the field of Gastronomy, stablishing as the research problem the concepts present in the academic education offered by UNISC in the Superior Course in Gastronomy Technology. This research consists in a case study that analyses the course’s Pedagogical Political Project, including modifications made to the document since the year it was developed, changes presented in the curriculum, as well as the importance of the mentioned course for the community of the city of Santa Cruz do Sul. It is understood that Gastronomy related fields of study are wide, however, they are still relatively new and expanding, what expresses the importance of the referred study for the area. When reflecting on the education of professionals of the food industry and the issues surrounding the human act of eating beyond its biological functions, it is possible to notice the social practices that embrace a significant portion of living as a society. Therefore, the need to analyze the act of eating in a way that surpasses the marketing necessities is emphasized in this research.